A reflective account of facilitator practice improvement in a leadership development programme in the Technical and Vocational Education and Training (TVET) sector - Adams, Tania Bernadette (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.